Fetal acidosis in a sheep model: can we perform a second day of protocol in order to reduce the numbers of animals needed? - C. Pierre; L. Ghesquiere; J. De Jonckheere; E. Aubry; D. Sharma; P. Deruelle; L. Storme; V. Houfflin-Debarge; C. Garabedian (IMR Press, 2020)
Objective: To determine if a model of acidosis caused by occlusion of the umbilical cord could be repeated in the same sheep in ethicaly order to reduce the number of animals needed. Method: To obtain fetal acidosis, 1 min of total umbilical cord occlusion (UCO) every 2.5 min was performed on fetal sheep (n=7) until pH reached 7.10. Chronic instrumentation regularly recorded arterial blood gas and hemodynamic parameters. The occlusions were repeated to compare the data between the 2 days for each animal. Results: At the end of the UCO period, fetal acidosis was obtained with a pH 7.14 on day 1 (D1) and 7.06 on day 2 (D2). At baseline, fetuses were more hypotensive at D2 (41 mmHg vs 44 mmHg on D1, p < 0.05). During the UCO period, there was no significant difference in blood gas and hemodynamic data between D1 and D2. Conclusion: To reduce the number of animals needed, performing a second experiment on the same animal appears possible even if results must be interpreted cautiously when severe acidosis is reached.